Motor corticospinal excitability: a novel facet of pain modulation?. (March 2019) - Granovsky, Yelena; Sprecher, Elliot; Sinai, Alon
Abstract: Introduction: Increase in excitability of the primary motor cortex (M1) is associated with pain inhibition by analgesics, which is, in turn, associated with the psychophysical antinociceptive pain modulation profile. However, the relationship between neurophysiological M1 excitability and psychophysical pain modulation has not yet been explored. Objectives: We aim to study these relationships in healthy subjects. Methods: Forty-one young healthy subjects (22 women) underwent a wide battery of psychophysical testing that included conditioned pain modulation (CPM) and pain temporal summation, and a transcranial magnetic stimulation neurophysiological assessment of the motor corticospinal excitability, including resting motor threshold, motor-evoked potentials (MEPs), and cortical silent period. Results: Increased motor corticospinal excitability in 2 parameters was associated with more efficient CPM: (1) higher MEP amplitude ( r = −0.574; P _Bonferroni = 0.02) and (2) longer MEP duration ( r = −0.543; P _Bonferroni = 0.02). The latter also correlated with the lower temporal summation magnitude ( r = −0.421; P = 0.007); however, on multiplicity adjustment, significance was lost. Conclusions: Increased corticospinal excitability of the primary motor cortex is associated with more efficient inhibitory pain modulation as assessed by CPM, in healthy subjects. Motor-evoked potential amplitude and duration may be considered as an additional, objective and easy to measure parameter to allow for better individual assessment of pain modulation profile.